PERAN MEDIA MASSA DALAM MELAKUKAN SOSIALISASIWAWASAN MULTIKULTURALISME (Studi Koran Gorontalo Pos dan Radio Republik Indonesia di Gorontalo) - Abdul Kadir M (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Gorontalo. Focus study is GorontaloPos Newspaper and Radio Republik Indonesia (RRI) Gorontalo. Thisresearch aims to describe the role mass media in socializingmulticulturalism idea. This research use qualitative method. Data wascollected by using interview and article searching. Then, analyzed bydescription analysis.This research indicates that the role mass media in socializingmulticulturalism idea is very well. The forms of multiculturalism socializationare news, rubric perception, culture program, entertainmentand religious broadcast. The respond of people to mass media in socializingmulticulturalism, some of them optimism, some of them pessimism